Adhesion Molecule L1 Agonist Mimetics Protect Against the Pesticide Paraquat-Induced Locomotor Deficits and Biochemical Alterations in Zebrafish - Joseph, Thomson Patrick; Jagadeesan, Nataraj; Sai, Liu Yang; Lin, Stanley Li; Sahu, Sudhanshu; Schachner, Melitta (Frontiers in Neuroscience, 2020)
Besides several endogenous elements, exogenous factors, including exposure to pesticides, have been recognized as putative factors contributing to the onset and development of neurodegenerative diseases, including Parkinson’s disease (PD). Considering the availability, success rate, and limitations associated with the current arsenals to fight PD, there is an unmet need for novel therapeutic interventions. Therefore, based on the previously reported beneficial functions of the L1 cell adhesion molecule, we hypothesized that L1 mimetic compounds may serve to neutralize neurotoxicity triggered by the pesticide paraquat (PQ). In this study, we attempt to use PQ for inducing PD-like pathology and the L1 mimetic compounds phenelzine sulfate (PS) and tacrine (TC) as potential candidates for the amelioration of PD symptoms using zebrafish as a model system. Administration of PQ together with the L1 mimetic compounds PS or TC (250 nM) improved survival of zebrafish larvae, protected them from locomotor deficits and increased their sensorimotor reflexes. Moreover, application of PQ together with PS (500 nM) or TC (1000 nM) in adult zebrafish counteracted PQ-induced toxicity, maintaining normal locomotor functions and spatial memory in a novel tank and T-maze task tests, respectively. Both L1 mimetic compounds prevented reduction in tyrosine hydroxylase and dopamine levels, reduced reactive oxygen species generation, protected against impairment of mitochondrial viability, improved the antioxidant enzyme system and increased ATP levels. Altogether, our findings highlight the beneficial functions of the agonistic L1 mimetics PS and TC by improving several vital cell functions against PQ-triggered neurotoxicity.